Solid Waste Management for Circular Economy towards Sustainable Development of India (International Journal of Food and Nutritional Sciences, 2022)
In the modern world, solid waste management has strategic ramifications. The need to balanceenvironmental protection with economic growth is driving attention towards the non-linear economy'spotential. The management of solid and liquid wastes should focus on methods that treat, recycle, andreduce wastes by treating them like resources. This Research article‘s objective is to examine circulareconomy and ecological protection for sustainable environmental livelihood and its theoretical andpractical waste management is concerns from the standpoint of cross-disciplinary eco-economiccollaboration, using the concepts of the circular economy